2015
DOI: 10.3390/ijgi4042339
|View full text |Cite
|
Sign up to set email alerts
|

Bridge Performance Assessment Based on an Adaptive Neuro-Fuzzy Inference System with Wavelet Filter for the GPS Measurements

Abstract: This study describes the performance assessment of the Huangpu Bridge in Guangzhou, China based on long-term monitoring in real-time by the kinematic global positioning system (RTK-GPS) technique. Wavelet transformde-noising is applied to filter the GPS measurements, while the adaptive neuro-fuzzy inference system (ANFIS) time series output-only model is used to predict the deformations of GPS-bridge monitoring points. In addition, GPS and accelerometer monitoring systems are used to evaluate the bridge oscill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Based on (4) and (11), to estimate the element ( = − 1), the DANFIS output is calculated as follows [14,22]:…”
Section: Input Layer Input Mf Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Based on (4) and (11), to estimate the element ( = − 1), the DANFIS output is calculated as follows [14,22]:…”
Section: Input Layer Input Mf Layermentioning
confidence: 99%
“…Also, it is found that the nonlinear Hammerstein-Wiener model performance is better than the linear one [10]. On the other hand, the adaptive neurofuzzy inference system (ANFIS) is used widely for the designing of prediction's models; more details on the ANFIS model design and previous studies can be found in [11][12][13][14]. The performance of the ANFIS model is better with MISO variables [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Structural engineers are trying to seek some new test methods to overcome these challenges. Currently, the technique of Global Positioning System-Real Time Kinematic (GPS-RTK) is widely used in SHM (see, e.g., [3][4][5]). However, vibration signals collected by GPS-RTK are often embedded in various noises.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the number and type of MF are an important parameter in identifying the model selected. The second model is called ANFIS model, which is known as the best models used in previous research in controlled structures [1,12,24,25]. The number and type of MF and input time-delayed are main parameters for the ANFIS model as presented in [1].…”
Section: Training Setting Evaluationmentioning
confidence: 99%
“…In addition, four common MF types are evaluated in Table 3, and it can be seen that the sigmoid function has a good performance. The sigmoid function is presented in Equation (12).…”
Section: Training Setting Evaluationmentioning
confidence: 99%